‘The viceroys are disappearing from the roundabouts in Delhi’: British symbols of power in post-colonial India - McGarr, Paul M. (Cambridge Journals, 2015)
In the aftermath of the Second World War, as postcolonial regimes in Africa and Asia hauled down imperial iconography, to the surprise and approval of many Western observers, India evidenced little interest in sweeping away remnants of its colonial heritage. From the late 1950s onwards, however, calls for the removal British imperial statuary from India’s public spaces came to represent an increasingly important component in a broader dialogue between central and state governments, political parties, the media, and the wider public, on the legacy of British colonialism in the subcontinent. This paper examines the responses of the ruling Congress Party and the British government, between 1947 and 1970, to escalating pressure from within India to replace British statuary with monuments celebrating Indian nationalism. In doing so, it highlights the significant scope that existed for non-state actors in India and the United Kingdom with a stake in the cultural politics of decolonisation to disrupt the smooth running of bi-lateral relations, and, in Britain’s case, to undermine increasingly tenuous claims of continued global relevance. Post-war British governments believed that the United Kingdom’s relationship with India could be leveraged, at least in part, to offset the nation’s waning international prestige. In fact, as the fate of British statuary in India makes clear, this proved to be at least as problematic and flawed a strategy in the two decades after 1947, as it had been in those before.